A regional comparative study on the mismatch between population urbanization and land urbanization in China. - Xingfen Wang; Xindi Zhang (PLoS ONE, 2023)
By taking 31 provinces (municipalities/autonomous regions) in Mainland China as the object of research, and using the data on urban population and built-up area of each region from 2005 to 2019, this paper measures the dispersion coefficient of population urbanization and land urbanization in each region through models and visually expresses the level and type of imbalance between them to reveal the temporal and spatial characteristics of imbalance. The results of the research show that since China's state-owned land was sold through bidding, auction, and listing, the overall urbanization of the population and land development have become unbalanced. There is obvious regional and category difference in imbalance between population urbanization and land urbanization. The degree of imbalance increases from the central, eastern, northeastern to western regions. The remaining 29 regions are generally lagging in population urbanization except for Beijing and Hebei province. This imbalance is mainly caused by China's dual household registration system, dual land system and the asymmetrical tax distribution system between financial rights and administrative rights.